A Polish Renaissance - Jacobson, Bernard (20th century composers, 1996)
Yet the four Poles whose story is told here - Andrzej Panufnik (1914-91), Witold Lutoslawski (1913-94), Krzystof Penderecki (b. 1933), and Henryk Gorecki (b. 1933) - are noted for their development of radically differing creative approaches, in spite of a common national background